THE USE OF INFORMATION TECHNOLOGY IN CASTINGS PRODUCTION - I. J. Getsman; I. M. Zayats (Литьë и металлургия)
The technological processes of production of dispensable patterns, sand molds and cores on three-dimensional printers are considered.